Análisis del comportamiento de las exportaciones del Perú, periodo 2016 - 2020 - Slley Carihua, Irleys Winquer (2022)
The research work analysis of the Behavior of Peruvian exports, period 2016 - 2020. Loreto aims to analyze the evolution of exports from Peru, in the period 2016 - 2020, the research is descriptive level and cross non-experimental design , the population is made up of all the statistical records related to exports of traditional and non-traditional products from Peru in the 2016-2020 Period, which exist in the National Superintendency of Tax Administration and the BCRP; In the period of analysis, traditional exports reached the sum of US $ 158 million 543 thousand at FOB value, 60.6% higher than non-traditional exports which reached the sum of US $ 62 million 433 thousand at FOB value. Mining products are those that have more participation in the structure of the export of traditional products, in each year they represent more than 80%.